Yaroslav Chaban. Oleksandr Bezborod'ko as a leading diplomat and state official of the Russian Empire in the last quarter of the XVIII century - Chaban, Yaroslav (Young Scholars Grinchenko – Seton International Journal, 2021)
Abstract. In the last quarter of the 18th century the Russian Empire had one of the key position in the forefront of the political life of the Old World. Representatives of Ukrainian origin had not the least place in this process. They were allowed to participate in governing the state at the general imperial level for the first time since the Pereyaslav Council in 1654. One of such historical figures was Oleksandr Bezborodʹko (1747–1799), the member of the Little Russia board of Peter Rumyantsev, the State Secretary of Catherine the Great, the Chancellor, the Hofmeister, the Knight of the Order of Saint Andrew the Apostle the First-Called, the Order of Alexander Nevsky, the Order of Saint John of Jerusalem (Maltese Cross), the Order of Saint Vladimir, the son of Glukhov General Judge. However, despite the significant contribution of this historical figure, his personality is insufficiently studied due to the significant disproportionate research of the activities of Ukrainians in the highest circles of the Russian Empire in modern historiography. Thus, some historical personalities remain outside the research of modern historians, which, however, does not mean that their contribution to the developmet of Russian statehood is inferior to that of more famous figures. In our article, we drew attention to the person of Oleksandr Bezborod’ko. We considered the main directions of his activity in the foreign and domestic policy of the Russian Empire, in the field of culture and his support of the Ukrainian fellowship. Among the central issues of our study were the contribution of O.A. Bezborod’ko as the creator of the Declaration of Armed Neutrality in 1780 during the War of the North American colonies for Independence /the American War of Independence; his contribution as the creator of the Southern vector of the foreign policy of the Russian Empire in the alliance with the Austrian Kaiser Joseph II; his participation and contribution to the solution of the Crimean, Turkish and Polish issues; his development of the concept of the Greek project. We explored the career path of Oleksandr Bezborod’ko as a leading diplomat and a state official of the Russian Empire of the last quarter of the 18th century from the official of the Little Russia board of Peter Rumyantsev to the State Secretary of Catherine II, her main speaker and State Secretary, the Count, the member of the Board of Foreign Affairs, the Hofmeister, and the Prince, the Chancellor of the Russian Empire during the reign of Paul I. We highlighted the relationship of Oleksandr Bezborod’ko with Ukrainian fellowship, the attitude of the Chancellor to the Ukrainians, natives of Ukrainian lands, named these persons who made up his Ukrainian environment; we analyzed Bezborod’ko's activity in domestic politics, in the cultural sphere, in particular, in the historical field, we outlined the Chancellor's attitude to the Ukrainian lands and his typical manifestations of local patriotism; guided by existing concepts, we considered the figure of O.A. Bezborod’ko as a probable author of the anonymous work "History of the Rusiv" as the main document of the Ukrainian autonomy of the 18th – 19th centuries. Keywords: Oleksandr Bezborod’ko, foreign policy of the Russian Empire, Southern vector, Eastern question, Crimean question, Turkish question, Greek project, Polish question, the second half – the last quarter of the 18th century, Ukrainian fellowship of Oleksandr Bezborod’ko, "History of the Rusiv".